Effective Waste Water Treatment by the Application of Natural Coagulants. (20th September 2022) - Panwar, Kartika; Dadhich, Itika; Dave, Mayank; Sharma, Yagya; Shaik, Nagaraju
Abstract : The natural water contamination because of the population growth, industrialization, urbanization, sewage from households, industries, institutions, and hospitals, among other things, has increased. After using in various ways, this water turns into wastewater, completing the hydrological cycle. Waterways that are contaminated pose numerous hazards to health and environment. As a result, contaminants must be removed. Coagulation is an effective basic chemical treatment technique that could be used to remediate such pollutants. The majority of people in rural areas are compelled to rely on easily accessible sources, which are typically of low quality and expose them to waterborne diseases, due to the high expense of chemical coagulant-treated water. Natural coagulant, a naturally occurring, plant-based coagulant, can then be used to reduce turbidity during the coagulation and flocculation stage of wastewater treatment. Chemical coagulants may be substituted with natural coagulants. It reduces turbidity while also being ecologically beneficial, serving a dual purpose. In order to solve turbidity concerns, substantial research is needed to find and adopt new techniques for water purification that are less expensive, need less energy, use fewer chemicals, and have a less negative impact on the environment. This study's objectives included evaluating the viability and efficacy of using natural coagulants in place of commonly used synthetic coagulants such aluminum sulphate as well as optimizing the coagulation procedure.